Considerações sobre abordagens de linguagem oral e escrita e variação nos livros didáticos voltados para o ensino fundamental - ciclo I - Pereira, Aparecida Gonçalves (2008)
The present study focuses and discusses some pedagogic directions which could be detected in Brazilian textbooks designed for the teaching of the mother tongue, i.e., the so-called oral and written language. The following questions guided the investigation carried on in the research: (1) Are issues concerning language variation considered in the textbooks under analysis? (2) Is close attention paid to the complex relations held between oral and written language? (3) Do the textbooks carefully explore the trends followed in the students construction of orthographic learning? The theoretical sources implied either to pose or to examine the textbooks selected here were those which traditionally deal with topics which underly the above questions, that is: Sociolinguistics, Applied Linguistics and Language Teaching Pedagogy. Those areas of knowledge may help understand and the critical moment of the Brazilian Education System and also virtually affect it in a fruitful way since they have strong theoretical and methodological resources to contribute to the building up of more solid public educational politics. In this study, textbooks are seen as the privileged loci of pedagogic frameworks and didactic tendencies. One can thus easily grasp why this study has chosen textbooks devoted to the teaching of oral and written language as its empirical data to investigate the pedagogic proposals suggested. It could be concluded that in the two textbooks, here analyzed, not only their specific content matters and the themes approached were highly appropriate but also the activities devised were not blind to the problems raised in this research